1980
DOI: 10.1113/jphysiol.1980.sp013092
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin inhibits the release and action of secretin on pancreatic secretion in the dog.

Abstract: SUMMARY1. Pancreatic bicarbonate and protein secretion as well as immuno-reactive plasma secretin concentration in response to a meal, duodenal acidification and exogenous secretin or octapeptide of cholecystokinin (OP-CCK) have been measured following administration of methionine-enkephalin in chronic pancreatic fistula dogs.2. Methionine-enkephalin inhibited pancreatic responses to both exogenous hormones (secretin and OP-CCK) and to endogenous hormones released from the gut by food or duodenal acidification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
2
5
0
Order By: Relevance
“…With reference to previous studies in various mammals, the present study has indicated that interspecific differences in the expression of Leu-Enk in mammalian pancreas are present. Similar immunohistochemical studies have identified Leu-Enk-IR nerve fibres near the acini, ducts, intrapancreatic neurons, and blood vessels of the pancreas of a number of species, including pigs (ADEGHATE et al, 1996), rats (SCHULTZBERG et al, 1980), guinea pigs (YALCIN, 1990;SCHULTZBERG et al, 1980) and dogs (CHEY et al, 1980). The present study provides an analysis of the distribution of LeuEnk-IR structures in the pancreas of sheep, and revealed that SOM, SP and GAL are coexpressed with Leu-Enk.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With reference to previous studies in various mammals, the present study has indicated that interspecific differences in the expression of Leu-Enk in mammalian pancreas are present. Similar immunohistochemical studies have identified Leu-Enk-IR nerve fibres near the acini, ducts, intrapancreatic neurons, and blood vessels of the pancreas of a number of species, including pigs (ADEGHATE et al, 1996), rats (SCHULTZBERG et al, 1980), guinea pigs (YALCIN, 1990;SCHULTZBERG et al, 1980) and dogs (CHEY et al, 1980). The present study provides an analysis of the distribution of LeuEnk-IR structures in the pancreas of sheep, and revealed that SOM, SP and GAL are coexpressed with Leu-Enk.…”
Section: Discussionsupporting
confidence: 80%
“…It has been postulated that Leu-Enk plays a role in the modulation and regulation of pancreatic hormone secretion (MILLAN and HERZ, 1985). The expression of Leu-Enk has been shown in the endocrine pancreas of various species, such as rats (TIMMERS et al, 1989;KHAWAJA et al, 1990;ADEGHATE and PONERY, 2001), guinea pigs (CETIN, 1990), pigs (ADEGHATE et al, 1996), cats (LARSSON, 1979) and dogs (CHEY et al, 1980), but sheep so far have not attracted researchers' interest. Therefore, the aim of the present immunofluorescence study was to examine the distribution pattern of neuronal elements containing Leu-Enk in the ovine pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Loperamide significantly (P õ .05) not only interacts with peripheral opiate receptors in the colon but also with opiate receptors in the proximal part of attenuated maximum gallbladder contraction in response to AID Hepa 0032 / 5p24$$$621 07-10-97 11:52:27 hepa WBS: Hepatology of CCK. 40,41 According to our data, the evidence in humans is otherwise because the release of CCK in response to a meal is enhanced by loperamide. A prolonged contact time between stimulating nutrients and CCK-secreting cells may be responsible for this enhanced release of CCK by loperamide because loperamide delays the passage of fluid through the intestine.…”
Section: Pmol/l) Duringmentioning
confidence: 99%
“…It has a powerful opiate-like effect and participates in the control of a wide variety of motor and secretory functions in the gastrointestinal tract (21). MEK has been shown to exert an inhibitory action on pancreatic exocrine secretion stimulated by duodenal acidification, exogenous secretin, and CCK in the dog (4). The inhibition by MEK appears to be caused, at least in part, by a direct effect on the exocrine pancreas.…”
mentioning
confidence: 99%
“…The inhibition by MEK appears to be caused, at least in part, by a direct effect on the exocrine pancreas. In addition, the release of secretin, and perhaps CCK, was also reduced by MEK in the dog (4). Konturek et al (12) reported that MEK inhibited pancreatic secretion elicited by sham feeding or exogenous secretin and CCK in humans that was reversed by naloxone.…”
mentioning
confidence: 99%